Pengaruh Persepsi Kemanfaatan, Persepsi Kemudahan, Persepsi Kepercayaan Dan Persepsi Risiko Terhadap Minat Mahasiswa Dalam Penggunaan Internet Banking Pada PT Bank BNI KCU Mattoangin Makassar - Husni, M. Fahrul; Nurdin, Maryam; Saeni, Nuraeni; Krisnanto, Budhi; HS, Elsa Mayuri (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
This study aims to determine the effect of perceived usefulness, perceived ease of use, perceived trust and perceived risk on student interest in PT Bank Negara Indonesia (Persero) Tbk. KCU Mattoangin Makassar. The analysis method used in this research is quantitative descriptive analysis method. The analytical tool used is multiple linear regression with the IBM SPSS Version 25.0 tool. From the proposed hypothesis test, the partial test research results show a positive and significant value for perceived usefulness, perceived convenience, perceived trust that it affects student interest in using mobile banking while perceived risk shows a negative and significant value. Simultaneously, the effect of perceived benefits, perceived convenience, perceived trust and perceived risk has a significant effect on customer interest and the R square value of 0.388 or 38.8% of the independent variable explains the dependent variable.